Phase I/II study of sorafenib in combination with temsirolimus for recurrent glioblastoma or gliosarcoma: North American Brain Tumor Consortium study 05-02 - Lee, Eudocia Q. (Oxford University Press, 2012)
The activity of single-agent targeted molecular therapies in glioblastoma has been limited to date. The North American Brain Tumor Consortium examined the safety, pharmacokinetics, and efficacy of combination therapy with sorafenib, a small molecule inhibitor of Raf, vascular endothelial growth factor receptor 2, and platelet-derived growth factor receptor–β, and temsirolimus (CCI-779), an inhibitor of mammalian target of rapamycin. This was a phase I/II study. The phase I component used a standard 3 × 3 dose escalation scheme to determine the safety and tolerability of this combination therapy. The phase II component used a 2-stage design; the primary endpoint was 6-month progression-free survival (PFS6) rate. Thirteen patients enrolled in the phase I component. The maximum tolerated dosage (MTD) for combination therapy was sorafenib 800 mg daily and temsirolimus 25 mg once weekly. At the MTD, grade 3 thrombocytopenia was the dose-limiting toxicity. Eighteen patients were treated in the phase II component. At interim analysis, the study was terminated and did not proceed to the second stage. No patients remained progression free at 6 months. Median PFS was 8 weeks. The toxicity of this combination therapy resulted in a maximum tolerated dose of temsirolimus that was only one-tenth of the single-agent dose. Minimal activity in recurrent glioblastoma multiforme was seen at the MTD of the 2 combined agents.